2020
DOI: 10.1186/s12889-020-09241-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between loneliness and blood glucose control in diabetes

Abstract: Background The data of the International Diabetes Federation show that about 463 million people have diabetes. Better understanding of psychosocial aspects of life with this disease has become one of healthcare priorities in this group of patients. The aim of this study was to assess the relationships between loneliness and blood glucose control in diabetic patients. Methods The study included 250 hospitalized patients with type 1 and 2 diabetes. The patients included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
5
1
2
Order By: Relevance
“…Loneliness has been associated with type 2 diabetes mellitus (DM) [153,154], hyperglycemia [26], and higher hemoglobin A1c (HbA1c) [155,156] and fasting blood sugar (FBS) [25] levels. Although some studies have found no significant relation between HbA1c and loneliness [157][158][159]. Social under-stimulation was associated with higher HbA1c levels [160].…”
Section: Markers Of Glycemic Controlmentioning
confidence: 92%
See 2 more Smart Citations
“…Loneliness has been associated with type 2 diabetes mellitus (DM) [153,154], hyperglycemia [26], and higher hemoglobin A1c (HbA1c) [155,156] and fasting blood sugar (FBS) [25] levels. Although some studies have found no significant relation between HbA1c and loneliness [157][158][159]. Social under-stimulation was associated with higher HbA1c levels [160].…”
Section: Markers Of Glycemic Controlmentioning
confidence: 92%
“…Higher triglyceride [26,162,163] and lower high-density lipoprotein (HDL) cholesterol (Chol) levels [26,162] were found in lonely people. However, total Chol, low-density lipoprotein (LDL) Chol, and non-HDL Chol levels were not correlated with loneliness [157]. In addition, lonely people had lower erythrocyte membrane proportions of Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA), which are omega-3 fatty acids [164].…”
Section: Markers Of Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that anxiety disorder, depressive symptoms and sleep quality became more prevalent and often worsened during COVID-19 as a result of the social isolation resulting from stay-at-home orders and closures have limited contact with family, friends and society [43]. Further, a recent study demonstrated that many adults with diabetes experience loneliness which is associated with other associated conditions such as lack of blood pressure control [44]. Although the study did not show a significant correlation between loneliness and blood glucose control, there is general concern because increased rates of mood disorders canalso lead to poor adherence of medications and worsening of risk factor control [45][46][47][48].…”
Section: Covid-19 and Mental Health Among Adults With Diabetesmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19) is a viral contagious disease. It is a single-stranded, enveloped RNA virus and it is named after its crownlike surface projections, which are seen in electron microscopy [1].…”
Section: Introductionmentioning
confidence: 99%